Cost optimization in serial kanban production systems using Markov models - Kesavan, Sangaradas; Fujiwara, Okitsugu; Pandey, P. C.; Vilas Wuwongse; The Government of Belgium (Bangkok : Asian Institute of Technology, 1993)
In this study we analyse the perfo1mance measures(inventory and back order) of the kanban discipline for a serial production system. There is a fixed number of kanbans in each stage. A part produced at preceding stage must acquire one of these kanbans to enter the stage and must contain to hold it throughout it sojourn there. Any unattached kanbans that are present in the stage are to be found on the bulletin board and are considered as requests for the parts produced at preceding stage. Inte1mediate-product inventory is divided into two parts, inventory at the output buffer and inventory at the succeeding stage's input queue. There are finite pools for raw parts preceding the first stage and finite demand following the final stage. We decompose each stage as a semi autonomous component and construct a stochastic model for each isolated stage. We explained the number of parts in the output buffer and the number of kanbans in the bulletin board as a Markov process and provide a scheme to analyse the performance measures of the system. In addition to this we introduce batch ordering policy with optimal re-ordering levels for raw parts.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Production engineering